Spatial planning based on urban waste-generating: A streetscape design perspective - Rusni, Nur Khafifah (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The concept of sustainable spatial planning can solve the limited land area of ​​DKI Jakarta Province. The increasing amount of waste generation in DKI Jakarta Province and the increasing population will cause the Bantargebang TPST's capacity to be insufficient soon. This research aims to analyze the amount of waste generation in DKI Jakarta Province. Method: The quantitative research approach uses mixed methods, including literature review and descriptive and spatial statistics. The data is secondary data from the Environmental and Cleanliness Information System of the DKI Jakarta Province Environmental Service (SILIKA). Findings: The results show the distribution of waste generation, presented in the form of a GIS (Geographic Information System) map. The results of this research show that the increase in the population of DKI Jakarta Province impacts waste generation; waste generation in 2019 increased by 54% in 2021. Recapitulation of waste generation in DKI Jakarta Province in 2021 Measurement Period I, the highest in East Jakarta, 2247.39 tonnes, and the lowest in Central Jakarta, 787 tons of waste. Conclusions: The study highlights that population growth directly increases waste production, with East Jakarta producing the most waste in 2021. The study highlights the need for sustainable spatial planning to address land scarcity and waste management challenges in the region. Novelty/Originality of this Article: This study introduces a GIS-based spatial analysis of waste generation in DKI Jakarta, highlighting the direct impact of population growth on waste production and the urgent need for sustainable spatial planning to address land scarcity and waste management challenges.